Pemanfaatan Limbah Beton Guna Meningkatkan Daya Dukung Tanah Lempung - Nurvianto, Rasuma Wahyu Tri, Anto Budi Listyawan, ST., MSc, Ir. Renaningsih, MT (2017)
Indonesia is Archipelago state structured on some islands with different soil structures. There is a soil problem in Sukodono of Sragen district in dry season, the soil is so hard, and when rany season the soil is muddy, and the way is easy to damage and the building on the soil is easy to happen crack. Based on the research was done, concrete waste became the material used to improve the soil, in this research with variation of mixture of 0%, 5%, 8%, and 10%, and done treatment of 4 and 6 days on mecanic sample. The result of origin fisis test got LL 65,04%, PL 20,53%, and PI 44,51%. The test of soil fisis charecter mixture increaded density, and platicity limit, wherease for water content, liquid limit, shrinkage limit, plasticity index, and passing on seive no.200 decreased. In AASHTO method classification, the origin soil and mixture of concrete waste included in specification of A-7-6, for USCS of the origin soil and mixture of concrete waste included CH specification is unorganic clay wiht high platicity.the result of compectness of optimum water content standard proctor and volume weight of dry soil increased in mixing of mixture and in treatment process. The result of volume weight of maximum dry soil and optimum water content which is the highest gotten soil with percentage of 10% with treatment of 6 days of 1,37 gr/cm3 and 27,1%. The result of CBR increased in addtion of mixture and treatment. The highest value of CBR was gotten with mixture of 10% with 6 days as high as 25%, the smallest value of CBR on the mixture of 5% without treatment as high as 20%. Keywords: clay, concrete waste, soil improvement, fisis character, bearing capacity